ON THE MOUTH-BREEDING CICHLID, TIL API A MOSSAMBICA PETERS - Panikkar, N K; Tampi, P R S (Indian Journal of Fisheries, 2016)
WHILE suggesting the possibilities of developing the low lying coastal areas into artificial marine fish farms, Panikkar (1952) stressed the need for selecting quick growing species for introduction into Indian waters so that a profitable yield will be possible within a reasonably short period. Species of Trichogaster and Tilapia were recommended for this purpose for the several saline coastal lagoons, more particularly the latter, as it can establish itself successfully in a variety of environmental conditions satisfying most of the requirements for culture in salt water. Since then efforts have been made to introduce the fish in South Indian waters